Parental support and bullying bystander behaviors in Chinese adolescents: Longitudinal mediation through social harmony - Jia, Xiaoyu; Wang, Jun; Zhang, Yuchi (Frontiers in Public Health, 2023)
Objectives Bullying in schools is a serious concern worldwide. The active defending or passive bystanding behaviors of bullying bystanders significantly contributes to the prevention of bullying. Relevant studies have increasingly adopted a social-ecological system approach in bullying research. However, the role of parental factors (microsystem) and cultural value (macrosystem) factors in adolescents' bullying behaviors in non-western culture contexts is unclear. Social harmony, which is closely related to social behavior, is a core value in Chinese culture. Exploring the role of social harmony in bullying bystanders in China could enhance our understanding of bullying, and enrich the diversity of the literature. This study aimed to examine the mediation effects of social harmony on the associations between parental support and the bullying bystanders among Chinese adolescents. Materials and methods The participants comprised 445 Chinese adolescents (mean age = 14.41, SD = 0.51) from Beijing City, China. A 17-month, two-point longitudinal study was conducted. Parental support, social harmony, and the behavior of bullying bystanders were evaluated at two time points. The hypothesized mediation model was examined using a structural equation modeling approach using bootstrapping techniques. Results The results showed that social harmony partly mediated the positive relationship between adolescents' parental support and active defending behaviors, and fully mediated the negative relationship between adolescents' parental support and passive bystanding behaviors. Conclusion These results highlight the importance of studying parental and cultural values in research on bullying bystanders.